Analisa Over Current Relay (OCR) dan Ground Fault Relay (GFR) pada Jaringan Distribusi 20 kV - Arya, Engla Harda; Ermawati, Ermawati; Machdalena, Machdalena; Hendri, Jhon (SURYA TEKNIKA, 2024)
In operation of the electric power system, disturbances often occur which can result in disruption of the distribution of electric power to consumers. The disturbances that often occur in the 20 kV medium voltage network distribution system are short circuit faults and overload faults. Protections used to prevent the disturbance from spreading and not disturbing healthy areas is the over current relay and ground fault relay. Based on the results of the researcht, showed that the relay coordination settings were OCR Incoming Primary Iset = 1818.65 A, Secondary Iset = 0.909 A, TMS = 0.199. In the OCR of the Primary Iset Feeder = 504 A, Secondary Iset = 1.26 A, TMS = 0.199, GFR Incoming Primary Iset = 144.19 A, Secondary Iset = 0.072 A, TMS = 0.238 and GFR of the Primary Iset Feeder = 140.19 A, Secondary Iset = 0.35 A, TMS = 0.23